Negative electrode for lithium secondary battery and secondary battery comprising same

By introducing carbon fibers into the negative electrode mixture layer of the lithium-ion battery and oriented them with a magnetic field, the problem of reducing the diffusion speed of lithium ions is solved, and the fast charging performance is significantly improved.

CN119230739APending Publication Date: 2024-12-31SK ON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311799780.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2023-12-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The negative electrode active substances of lithium-ion batteries are irregularly distributed during drying and calendering, resulting in a decrease in the diffusion speed of lithium ions and affecting the rapid charging performance of the battery.

Method used

Carbon fibers are introduced into the negative electrode mixture layer, with an average diameter of 5-20 μm, oriented in a vertical direction with respect to the negative electrode current collector, and oriented the negative electrode active material through a magnetic field to form a linear lithium ion movement path.

Benefits of technology

The movement speed of lithium ions is significantly improved, the fast charging performance is improved, and the movement path twist factor of lithium ions is reduced without affecting the battery capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230739A_ABST
    Figure CN119230739A_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode for a lithium secondary battery and a secondary battery comprising the same, and provides a negative electrode comprising: a negative electrode current collector; and a negative electrode mixture layer formed on at least one surface of the negative electrode current collector, in which the negative electrode mixture layer contains a negative electrode active material and carbon fibers, and the average diameter of the cross section of the carbon fibers is 5-20 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode for a lithium secondary battery and a secondary battery comprising the negative electrode. Background Art

[0002] In recent years, as the electric vehicle market has expanded, interest in lithium secondary batteries has also been rapidly increasing. For such electric vehicles, the fact that it takes time to charge the battery is considered a disadvantage, so there is a high interest in fast charging, and a lot of research is being conducted to shorten the charging time.

[0003] Generally, in the case of a negative electrode of a lithium-ion battery, particles such as a negative electrode active material constituting an electrode mixture are irregularly distributed during a drying process for removing an organic solvent and a rolling process for achieving a specified electrode density, and thus pores formed between particles existing in an electrode mixture layer are also unevenly distributed.

[0004] In particular, the negative electrode active material particles such as anisotropic graphite used as negative electrode active materials are oriented in a horizontal direction relative to the electrode current collector, thereby increasing the movement path of lithium ions in the negative electrode mixture layer and slowing down the diffusion of lithium ions, thereby causing polarization of the battery and ultimately leading to a decrease in battery performance.

[0005] In recent years, in order to improve the problem of reduced diffusion rate of lithium ions due to horizontal orientation of negative electrode active materials as described above, the magnetic properties of anisotropic graphite used as negative electrode active materials are used to improve orientation. For this purpose, a technology that shortens the movement path of lithium ions by applying a magnetic field to orient vertically relative to the current collector is being applied to the manufacture of negative electrodes.

[0006] However, due to the shape of the graphite negative electrode active material or the overlap between the negative electrode active materials, the lithium ion movement path is not linear, and some lithium ion movement paths are severely bent or the movement paths may be blocked. Therefore, the fast charging performance brought about by the shortening of the lithium ion movement path has certain limitations. Summary of the invention

[0007] Technical issues to be solved

[0008] According to a specific embodiment of the present invention, a negative electrode is provided which can further increase the diffusion rate of lithium ions during rapid charging.

[0009] In addition, according to another specific embodiment of the present invention, a secondary battery including the negative electrode is provided.

[0010] Technical Solution

[0011] One aspect of the present invention provides a negative electrode. According to a specific embodiment, the negative electrode includes: a negative electrode collector; and a negative electrode mixture layer formed on at least one side of the negative electrode collector, wherein the negative electrode mixture layer contains a negative electrode active material and carbon fiber, the average diameter of the cross section of the carbon fiber is 5-20 μm, and is oriented in a direction perpendicular to the negative electrode collector.

[0012] As an embodiment, the negative electrode mixture layer may include: a first layer, the first layer including a first surface in contact with the negative electrode current collector; and a second layer, the second layer including a second surface outside the negative electrode mixture layer located opposite to the first surface, wherein the first layer may contain carbon fiber.

[0013] As an embodiment, one or more negative electrode mixture layers may be further included between the first layer and the second layer, and in two adjacent layers, the carbon fiber content of the negative electrode mixture layer close to the first side may be higher than that of the negative electrode mixture layer close to the second side.

[0014] As an embodiment, the second layer may or may not contain carbon fibers.

[0015] As an embodiment, the average length of the carbon fibers may be 30-150 μm.

[0016] As an embodiment, the carbon fiber may have a carbon fiber weight of 1.75-1.93 g / cm 3 density.

[0017] As an embodiment, the content of the carbon fiber may be 0.5-10 wt % relative to the total weight of the negative electrode mixture layer.

[0018] As an embodiment, the negative electrode active material may include graphite.

[0019] As an embodiment, the preferred orientation (P / O) value of the negative electrode according to XRD analysis may be 0.45 or less.

[0020] As an embodiment, the negative electrode active material may have an orientation perpendicular to the negative electrode current collector.

[0021] As an embodiment, the negative electrode may have an average tortuosity factor value of 1.24 or less.

[0022] As an embodiment, the negative electrode may further include a conductive agent, and the conductive agent may further include at least one selected from a particulate conductive agent having an average particle diameter of 10-500 nm and a fibrous conductive agent having an average fiber diameter of 10-500 nm.

[0023] In addition, as one aspect, the present invention provides a secondary battery including a positive electrode and any one of the above-mentioned negative electrodes.

[0024] Beneficial Effects

[0025] According to one embodiment of the present invention, by including pores having linearity in the negative electrode mixture layer, the movement speed of lithium ions at the time of rapid charge can be significantly improved.

[0026] The negative electrode according to a specific embodiment of the present invention can be widely used in green technology fields such as secondary batteries, energy storage devices, etc. In addition, the secondary battery including the negative electrode according to a specific embodiment of the present invention can be used for eco-friendly electric vehicles, hybrid vehicles, etc. that suppress air pollution and greenhouse gas emissions to prevent climate change. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a diagram schematically showing the migration path of lithium ions in a negative electrode that does not include carbon fibers.

[0028] Figure 2 This is a diagram schematically showing the migration path of lithium ions in a negative electrode that does not include carbon fibers and in which the negative electrode active material is oriented by a magnetic field.

[0029] Figure 3 is a diagram schematically showing a migration path of lithium ions in a negative electrode according to a specific embodiment including carbon fibers.

[0030] Figure 4 : is a diagram schematically showing a migration path of lithium ions in a negative electrode according to a specific embodiment, which includes carbon fibers and has a negative electrode active material oriented by a magnetic field.

[0031] Figure 5 This is a SEM photograph of the carbon fiber used in Example 1.

[0032] Figure 6 The figures show the cross-sectional structures of negative electrodes produced in Example 1 and Comparative Example 1 analyzed by XRM, wherein (a) is the negative electrode of Example 1, and (b) is the negative electrode of Comparative Example.

[0033] Description of Reference Numerals

[0034] 3: Negative electrode active material

[0035] 5: Carbon fiber

[0036] 11: Negative electrode current collector

[0037] 13: Negative electrode mixture layer

[0038] 100: Negative electrode

[0039] P: Moving path DETAILED DESCRIPTION

[0040] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings, but this is merely an exemplary description, and the present invention is not limited to the specific embodiments described exemplarily.

[0041] Generally, in the negative electrode of a lithium secondary battery, a negative electrode mixture layer containing a graphite-based negative electrode active material is formed on a negative electrode current collector, and pores are formed between particles of the graphite-based negative electrode active material in the negative electrode mixture layer, and the pores serve as paths for the movement of lithium ions during the charge and discharge process of the battery.

[0042] The negative electrode is manufactured by dispersing a slurry prepared by dispersing an electrode mixture containing a graphite-based negative electrode active material, a binder and a conductive agent in an organic solvent on a current collector surface, evaporating the organic solvent, and increasing the electrode density by rolling. However, during the drying process of evaporating the organic solvent and the rolling process, the particles constituting the electrode mixture, especially the negative electrode active material such as anisotropic graphite, are oriented in a horizontal direction and are irregularly distributed. Due to the horizontal orientation and irregular distribution as described above, the pores formed between the particles in the negative electrode mixture layer are also unevenly distributed.

[0043] Figure 1 Schematically shows the distribution of the negative electrode active material and pores of the negative electrode mixture layer as described above. Figure 1 As shown, the negative electrode active material 3 and the pores in the negative electrode mixture layer 13 formed on the negative electrode current collector 11 are unevenly distributed and horizontally oriented, thereby causing the tortuosity of the pores in the negative electrode mixture layer to become higher and greatly increasing the distance of the moving path P for the movement of lithium ions, thereby reducing the rapid charging performance of the battery.

[0044] During the charging process, the higher the rate, the higher the tortuosity factor of the pores in the negative electrode mixture layer will act as a barrier to the conduction of lithium ions, thereby causing polarization of the battery and resulting in reduced cell performance.

[0045] In recent years, in order to improve the problem of reduced diffusion rate of lithium ions due to horizontal orientation of negative electrode active materials as described above, a technology of shortening the movement path of lithium ions by applying a magnetic field to orient vertically relative to the current collector is being applied to the manufacture of negative electrodes. By utilizing the magnetic properties of anisotropic graphite used as a negative electrode active material, applying a magnetic field after coating the negative electrode mixture on the negative electrode current collector, the negative electrode active material can be oriented vertically relative to the negative electrode current collector, and the graphite in the negative electrode mixture layer is oriented in a direction vertical to the negative electrode current collector as described above, so that the effect of shortening the movement path of lithium ions can be obtained.

[0046] However, due to the overlap of negative electrode active material particles in the negative electrode mixture layer or the shape of the graphite negative electrode active material itself, the lithium ion migration path may not be linear even if a magnetic field is applied. Figure 2 It is schematically shown in FIG. Figure 2 Schematically showing the negative electrode active material 3 and pores in the negative electrode mixture layer 13 in the negative electrode obtained by applying a magnetic field, as shown in FIG. Figure 2 As shown, the lithium ion movement path P is not linear, and part of the lithium ion movement path P is severely curved or the movement path P may be blocked. Therefore, the improvement of the fast charging performance brought about by the shortening of the lithium ion movement path has certain limitations.

[0047] The present invention provides a negative electrode which can improve the rapid charging performance by shortening the migration path of lithium ions.

[0048] The negative electrode according to the present invention includes: a negative electrode collector; and a negative electrode mixture layer formed on at least one side of the negative electrode collector and containing a negative electrode active material.

[0049] As non-limiting examples of the negative electrode current collector, a negative electrode current collector selected from copper foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, and combinations thereof may be used.

[0050] The thickness of the negative electrode current collector is not particularly limited, and may be, for example, 10-50 μm.

[0051] As a specific embodiment, a negative electrode mixture in a slurry phase is coated on the surface of the negative electrode collector and dried to form a negative electrode mixture layer, wherein the negative electrode mixture includes a negative electrode active material and carbon fibers.

[0052] The negative electrode active material can be a material that allows lithium ions to be intercalated and deintercalated. The negative electrode active material can include a carbon-based negative electrode active material. As long as the carbon-based negative electrode active material is a material commonly used in manufacturing the negative electrode of a lithium ion secondary battery, it can also be suitably used in the present invention, and thus is not particularly limited, but can be graphite, specifically artificial graphite. As the negative electrode active material, the crystallographic characteristics of the particles of the crystalline carbon-based material, which is artificial graphite or a mixture of artificial graphite and natural graphite, are more developed. Therefore, compared with the amorphous carbon-based active material, the orientation characteristics with respect to an external magnetic field can be further improved, and thus the orientation of the pores in the negative electrode mixture layer can be improved.

[0053] The carbon-based negative electrode active material can be used by mixing the artificial graphite and natural graphite. When the artificial graphite and natural graphite are used by mixing, the artificial graphite and natural graphite can be mixed at a weight ratio of 70:30 to 95:5.

[0054] The shape of the artificial graphite or natural graphite is not particularly limited, and can have various shapes such as amorphous, plate-like, flaky, spherical, fibrous, etc., and can be a combination thereof.

[0055] While the negative electrode mixture contains the carbon-based negative electrode active material, it can further contain at least one second negative electrode active material selected from a Si (silicon)-based negative electrode active material, a Sn (tin)-based negative electrode active material, or a lithium vanadium oxide negative electrode active material as needed. When the negative electrode mixture further contains the second negative electrode active material, the second negative electrode active material can be contained in a range of 1-50% by weight relative to the total weight of the negative electrode active material.

[0056] The Si-based negative electrode active material can be Si, a Si-C composite, SiO x (0 < x < 2), a Si-Q alloy, where Q can be an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof other than Si, and can specifically be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0057] The Sn-based negative electrode active material may be Sn, SnO2, or a Sn-R alloy, and R is not Sn or Si, and R may be an element selected from alkali metals, alkaline earth metals, elements of Group 13, elements of Group 14, elements of Group 15, elements of Group 16, transition metals, rare earth elements, and combinations thereof, and may be specifically selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof. Furthermore, at least one of them may be mixed with SiO2 for use.

[0058] The content of the negative electrode active material may be 94-98% by weight relative to the solid weight of the negative electrode mixture.

[0059] The negative electrode mixture of the present invention contains carbon fibers, which function as a conductive agent and can improve the degree of tortuosity of the lithium ion movement path in the negative electrode mixture layer, thereby making the lithium ion movement path simpler and more linear and helping to shorten the movement path.

[0060] The effect of simplifying and shortening the lithium ion migration path by the carbon fibers can be obtained not only when the negative electrode active material is oriented by a magnetic field, but also in a negative electrode without oriented negative electrode active material.

[0061] Specifically, Figure 3 A specific embodiment of a negative electrode having a negative electrode mixture layer containing carbon fibers is schematically shown in FIG. Figure 3 As shown, the carbon fiber 5 is present in the negative electrode mixture layer 13 formed on the negative electrode current collector 11, so pores providing a lithium ion movement path P can be formed along the outer side of the carbon fiber 5 between the negative electrode active material 3 particles. At this time, at least a portion of the pores providing a lithium ion movement path P is formed along the carbon fiber 5, so the movement path P can be simplified and shortened.

[0062] Furthermore, the carbon fibers can alleviate distortion of the migration path of lithium ions that may occur in a negative electrode in which a negative electrode active material is oriented in a direction perpendicular to a negative electrode current collector by applying a magnetic field or the like.

[0063] For example, Figure 4 A specific embodiment of a negative electrode having a negative electrode mixture layer containing carbon fibers and oriented is schematically shown in FIG. Figure 4As shown, in the case of the negative electrode 100 having the negative electrode mixture layer 13 for orienting the negative electrode active material on the negative electrode current collector 11, the carbon fiber 5 is also included in the negative electrode mixture layer 13, so that a linear pore providing a lithium ion movement path P can be formed between the particles of the negative electrode active material 3 along the outer side of the carbon fiber 5. Therefore, the lithium ion movement path P is further formed into a linear shape, so that the lithium ion movement path P can be simplified and shortened.

[0064] In the present invention, the "vertical direction" refers to a direction perpendicular to the plane of the negative electrode current collector. However, the vertical direction is not limited to being oriented at 90° relative to the negative electrode current collector, for example, it may include being oriented at 30° or more, preferably oriented at 45° or more, and more preferably oriented at 60° or more.

[0065] like Figure 3 and Figure 4 As shown, by including the carbon fiber 5 in the negative electrode mixture layer 13, a linear movement path P can be formed along the periphery of the carbon fiber 5, thereby Figure 1 and Figure 2 Compared with the curved or Z-shaped moving path P shown in the negative electrode, the tortuosity factor, that is, the degree of bending, can be significantly improved. Furthermore, a straight moving path P can be provided in a direction perpendicular to the negative electrode current collector 11 according to the situation. Therefore, the negative electrode according to a specific embodiment can obtain the effect of shortening the moving path of lithium ions, so the fast charging performance can be improved.

[0066] In order to provide a linear lithium ion movement path as described above, the carbon fiber may have a mechanical strength that is not easily bent by the solid matter constituting the negative electrode mixture, especially a mechanical strength that is not easily bent by the negative electrode active material. Therefore, the carbon fiber is not limited thereto, but the average thickness may be in the range of 5-20 μm. When the average thickness of the carbon fiber is less than 5 μm, it may be difficult to provide a linear movement path. When the average thickness of the carbon fiber exceeds 20 μm, the volume ratio of the active material in the electrode mixture layer is reduced, which may result in a decrease in capacity. In addition, the number of carbon fibers that can be included in the electrode mixture layer is reduced, which may be detrimental to providing linear pores.

[0067] In this respect, it is different from the carbon fiber usually used as a conductive agent in the electrode active material. In order to provide good conductivity, the carbon fiber usually provided as a conductive agent can use a carbon fiber with a smaller thickness than the carbon fiber used in the present invention to provide linear pores, for example, a carbon fiber with a thickness of 500nm or less can be used, for example, a carbon fiber with a thickness in the range of 10-500nm, 50-500nm, 50-300nm or 100-200nm.

[0068] The carbon fiber is not limited thereto, but may be a carbon fiber having a length of 30 μm or more. When the length of the carbon fiber is less than 30 μm, a linear lithium ion migration path may not be formed.

[0069] In addition, the carbon fiber is not limited thereto, but the length of the carbon fiber may be less than or equal to the thickness of the negative electrode mixture layer. When the length of the carbon fiber is longer than the thickness of the negative electrode mixture layer, it may protrude from the surface layer of the negative electrode mixture layer, and may penetrate the separator and directly contact the positive electrode. Therefore, the length of the carbon fiber may vary according to the thickness of the negative electrode mixture layer, for example, the length of the carbon fiber may be less than 150 μm, less than 120 μm, less than 100 μm, or less than 80 μm.

[0070] The content of the carbon fiber may be 0.5-10% by weight relative to the total weight of the negative electrode mixture layer, but is not limited thereto. For example, the content of the carbon fiber may be 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, 2% by weight or more, or 2.5% by weight or more, and may be 10% by weight or less, 7% by weight or less, 5% by weight or less, 4% by weight or less, or 3% by weight or less. When the content of the carbon fiber is less than 0.5% by weight, it may not be sufficient to form linear pores that provide a path for lithium ion movement in the entire region of the negative electrode mixture layer, and when the content of the carbon fiber exceeds 10% by weight, the content of the negative electrode active material is reduced, thereby possibly resulting in a reduction in capacity.

[0071] In a specific embodiment, the negative electrode mixture may include a binder. The binder serves to bind the negative electrode active material particles to each other and to bind the negative electrode active material to the negative electrode current collector. The binder may be a water-dispersible binder or a water-soluble binder.

[0072] The adhesive is not limited to this, but the adhesive can be listed as styrene-butadiene rubber, acrylated styrene-butadiene rubber (SBR), nitrile rubber, acrylic rubber, butyl rubber, ethylene-propylene copolymer, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, ethylene-propylene-diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol resin, acrylate-based resin, which can be used alone or in combination of two or more.

[0073] The content of the binder in the negative electrode active material layer may be 1.5-3% by weight relative to the solid weight of the negative electrode mixture.

[0074] In addition to the binder, a thickener may be included to adjust the viscosity of the negative electrode mixture slurry. The thickener may include a cellulose-based compound, for example, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. The alkali metal may use Na, K, or Li.

[0075] The content of the thickener may be 0.1-3 parts by weight relative to 100 parts by weight of the negative electrode active material.

[0076] The negative electrode mixture according to the present invention may include a conductive agent to impart conductivity to the electrode. The conductive agent can be used without restriction as long as it is a conductive agent commonly used in secondary batteries, for example, natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, acetylene carbon black, thermal black, channel black, carbon fiber, carbon nanotube, graphene and other carbon-based materials; copper, nickel, aluminum, silver, tin, tin oxide, tin phosphate, titanium carbonate, potassium titanate, LaSrCoO3, LaSrMnO3 and other perovskite materials such as metal or metal compound powder or fiber and other metal-based materials; polyphenyl derivatives and other conductive polymers; or conductive materials containing mixtures thereof.

[0077] When a silicon-based negative electrode active material is included as the negative electrode active material, carbon nanotubes may be included as the conductive agent. When the silicon-based negative electrode active material is used as the negative electrode active material and the carbon nanotubes are included as the conductive agent, even if the active material particles are separated due to volume expansion of the silicon-based negative electrode active material during charge and discharge, better conductivity can be provided.

[0078] When the conductive agent is a granular material such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, metal powder, etc., a material having an average particle diameter of 500 nm or less can be used, for example, a material having an average particle diameter of 10-500 nm can be used. In addition, when the conductive agent is a fibrous material such as carbon fiber, carbon nanotube or metal fiber, a material having an average fiber diameter of 500 nm or less can be used, for example, a material having an average fiber diameter of 10-500 nm can be used.

[0079] The content of the conductive agent may be 0.1-3 wt % relative to the solid weight of the negative electrode mixture.

[0080] The negative electrode mixture and the solvent are mixed to prepare a slurry, and the negative electrode mixture slurry is coated on the negative electrode current collector. The solvent is not particularly limited, and water such as pure water, deionized water, and distilled water, and ethanol, isopropanol, methanol, acetone, n-propanol, tert-butanol, etc. can be used as the solvent.

[0081] The solvent may be used to make the solid content of the negative electrode mixture slurry 30-65% by weight. When the solid content of the slurry is less than 30% by weight, the viscosity of the slurry is low, so the slurry easily flows down, resulting in reduced operability, and in order to ensure a specified adhesion amount, the number of coatings of the slurry may be increased. When the solid content of the slurry exceeds 65% by weight, the viscosity of the slurry is high, resulting in poor spreadability of the slurry, so it may be difficult to form a mixture layer of uniform thickness, and operability may be reduced.

[0082] The present invention comprises the steps of coating the negative electrode mixture slurry on at least one side of a negative electrode current collector and applying a magnetic field.

[0083] The coating process can be carried out by gravure coating, slot extrusion coating, multi-layer simultaneous die coating, embossing, doctor blade coating, dip coating, bar coating, casting and the like, but is not limited thereto.

[0084] By applying the magnetic field, the negative electrode active material contained in the negative electrode mixture slurry can be oriented. Figure 4 As shown, the negative electrode active material can be oriented in a direction perpendicular to the negative electrode current collector. At this time, the carbon fibers in the negative electrode mixture layer can support the vertically oriented negative electrode active material and provide linear pores that can induce the movement path of lithium ions to be formed into a linear shape. Therefore, the movement speed of lithium ions can be further increased, thereby improving the fast charging characteristics.

[0085] For the magnetic field, in order to orient the carbon fibers as described above, a magnetic field of 1000-10000 Gauss can be applied. For example, the magnetic field can be above 1000 Gauss, above 2000 Gauss, or above 3000 Gauss, and can be below 10000 Gauss, below 9000 Gauss, below 8000 Gauss, below 7000 Gauss, or below 6000 Gauss.

[0086] The magnetic field is not particularly limited, for example, the magnetic field can be applied for more than 0.5 seconds and less than 10 seconds. For example, the magnetic field can be applied for more than 0.5 seconds, more than 1 second, more than 2 seconds, or more than 3 seconds, and can be applied for less than 10 seconds, less than 9 seconds, less than 7 seconds, less than 6 seconds, or less than 5 seconds.

[0087] As described above, the negative electrode mixture slurry may be coated on at least one side of the negative electrode current collector and dried after applying a magnetic field to orient the negative electrode active material or while applying a magnetic field to orient the negative electrode active material.

[0088] The drying is used to remove the solvent contained in the negative electrode mixture, and a conventional drying method may be applied, for example, hot air drying or the like may be applied.

[0089] The drying process is not particularly limited, but can be carried out, for example, at 60-180° C., preferably 70-150° C., for 20-300 seconds, for example, 40-240 seconds, 60-200 seconds.

[0090] After the drying, the step of rolling the negative electrode mixture layer formed by drying may be included. The rolling is a step of adjusting the thickness or density of the electrode mixture layer, and conventional methods such as roller pressing and flat pressing can be used. Although not limited to this, the thickness of each single side of the negative electrode mixture layer according to the rolling can be, for example, 20 μm or more and 120 μm or less, specifically, 40 μm or more and 100 μm or less, or 60 μm or more and 80 μm or less.

[0091] In addition, although not limited thereto, the negative electrode mixture layer may have a surface area of ​​1.5 g / cm 3 For example, the density can be 1.5 g / cm 3 Above and 2.2g / cm 3 Below or 1.5g / cm 3 Above and 2.0g / cm 3 the following.

[0092] The negative electrode mixture layer may be formed on either side of the negative electrode current collector or on both sides. Furthermore, the negative electrode mixture layer may be a single layer or may be two or more layers, for example, a multilayer such as two, three or four layers.

[0093] When forming a multilayer negative electrode mixture layer, it can be formed by continuously or discontinuously applying multiple negative electrode mixture slurries while drying and rolling. In this case, the process can be simplified by performing a drying process once. In addition, it can be formed by applying a first negative electrode mixture slurry and drying it, then applying a second negative electrode mixture slurry in turn and drying it and rolling it. As described above, when the drying process is divided into multiple times, the binder distribution of each layer can be controlled, so that the migration of the binder can be suppressed.

[0094] In the negative electrode according to the present invention as described above, a linear lithium ion path is provided in the negative electrode mixture layer, so the path for lithium ions to move into the negative electrode can be further shortened. By shortening the diffusion path of lithium ions as described above, the charge and discharge efficiency at high rates can be improved, so the fast charging performance can be improved.

[0095] When the negative electrode is a multilayer negative electrode including two or more negative electrode mixture layers on one side of a negative electrode current collector, the carbon fibers may be contained in all layers of the negative electrode mixture layers or may be contained in a part of the layers.

[0096] For example, as a specific embodiment, the negative electrode mixture layer may include: a first layer, the first layer including a first surface connected to the negative electrode current collector; and a second layer, the second layer including a second surface outside the negative electrode mixture layer located opposite to the first surface. In this case, the first layer may contain carbon fiber.

[0097] That is, when the negative electrode mixture layer is a multilayer negative electrode with more than two layers, the closer to the interior of the negative electrode mixture layer, that is, the closer to the negative electrode current collector in the negative electrode mixture layer, the more difficult the ion conduction of lithium ions may be. As described above, by including carbon fibers in the first layer of the negative electrode mixture layer located on the current collector side, the ion conduction of lithium ions can be further improved.

[0098] As another specific embodiment, when the negative electrode mixture layer is a multilayer of more than 3 layers, the content of carbon fiber between two adjacent negative electrode mixture layers may be different from each other. Specifically, the content of carbon fiber contained in the negative electrode mixture layer located on the collector side of the two layers may be more than the content of carbon fiber contained in the negative electrode mixture layer located on the surface side. That is, from the first layer including the first surface as the collector side toward the second layer including the second surface as the outer side of the negative electrode mixture layer, the content of carbon fiber contained in each layer may gradually decrease. Therefore, the content of carbon fiber contained in the second layer may be minimal or may not be included. Among them, the content may refer to weight %.

[0099] Under the same other conditions, the negative electrode including the carbon fiber according to the present invention can have a higher black and white value compared with the negative electrode not including the carbon fiber.

[0100] The black and white degree can be measured using a chromameter, for example, the dE value can be measured using a CR-410 device from Konica Minolta. Specifically, for the negative electrode before and after orientation as the measurement object, quantitative measurements are performed at 10 points in the width direction (minor axis direction) of the negative electrode at intervals of 10 mm using a black and white degree measuring instrument and using the color system of L* (black and white), a* (red and green), and b* (yellow and blue), and the average value of the values ​​can be expressed as dE, black and white degree.

[0101] The black-white degree represents the dE difference of the negative electrode surface and the orientation of graphite in the negative electrode can be confirmed from the dE value. The larger the black-white degree value, the better the orientation of the negative electrode active material in the direction perpendicular to the negative electrode current collector.

[0102] According to a specific embodiment, the black and white difference of the negative electrode according to whether it is magnetically oriented can be 1.5 or more, but it is not limited thereto. Therefore, compared with the negative electrode to which the magnetic field is not applied, as the negative electrode according to the present invention, the negative electrode obtained by applying the magnetic field can have a black and white value increased by more than 1.0.

[0103] Further, compared with a negative electrode not comprising carbon fiber, a negative electrode comprising carbon fiber according to a specific embodiment may have a higher black and white value. For example, compared with a negative electrode not comprising carbon fiber and oriented by applying a magnetic field, a negative electrode according to a specific embodiment comprising carbon fiber and oriented by applying a magnetic field may have a higher black and white value, for example, may have a black and white difference of about 1.5 or more.

[0104] In addition, compared with the negative electrode not containing carbon fiber and not applying a magnetic field, as a negative electrode according to a specific embodiment, the negative electrode containing carbon fiber and not applying a magnetic field can have a higher black and white value. For example, it can have a black and white difference of about 0.5 or more.

[0105] In the negative electrode according to a specific embodiment, the carbon fiber contained in the negative electrode mixture layer can provide a support for the negative electrode active material. When a magnetic field is applied to orient the negative electrode active material after the negative electrode mixture of the slurry phase is coated on the negative electrode current collector, the orientation of the negative electrode active material can be improved or maintained.

[0106] Therefore, as described above, the negative electrode obtained in one specific embodiment can have a higher degree of blackness and whiteness not only in the case where a magnetic field is applied but also in the case where a magnetic field is not applied, compared with the negative electrode not including carbon fibers.

[0107] According to a specific embodiment, the preferred orientation (Preferred Orientation, P / O) value of the negative electrode according to XRD analysis can be 0.45 or less. The P / O is measured by XRD and is a value for comparing the (002) peak intensity representing the degree of orientation in the horizontal direction relative to the current collector, which represents the orientation degree of the negative electrode active material. The smaller the P / O value, the more excellent the vertical orientation degree of the negative electrode active material can be evaluated.

[0108] In addition, the mean tortuosity value of the negative electrode according to the present invention may be 1.24 or less, more specifically 1.22 or less or 1.20 or less. The tortuosity factor is defined as Ls / Le, wherein Ls represents the thickness (bulk thickness) of the porous material (porous media), and Le represents the average distance (average of path length) traveled through the porous material.

[0109] The Le and Ls can be obtained by analyzing the structure using an X-ray microscope (XRM) for non-destructive high-resolution 3D imaging and then calculating the Le and Ls values ​​to obtain the tortuosity factor.

[0110] The smaller the average tortuosity factor value is, the more linear the migration path of lithium ions is, indicating that the degree of bending is smaller, and thus the rapid charging property can be improved by improving the mobility of lithium ions.

[0111] The negative electrode obtained by the present invention is alternately stacked with the positive electrode with the separator as the boundary to produce an electrode assembly, which is then inserted into a battery case and sealed, and an electrolyte is injected to produce a lithium secondary battery.

[0112] According to an exemplary embodiment, an electrode assembly may be formed by repeatedly arranging a positive electrode, a negative electrode and a separator. In some embodiments, the electrode assembly may be a winding type, a stacking type, a z-folding type, or a stack-folding type.

[0113] Hereinafter, the positive electrode will be described in more detail.

[0114] The positive electrode is not particularly limited, but may be a positive electrode formed by coating a positive electrode mixture on at least one side of a positive electrode current collector and drying and rolling the mixture to form a positive electrode mixture layer. Any positive electrode commonly used in secondary batteries may be applicable to the present invention.

[0115] The positive electrode mixture may include a positive electrode active material, a binder, and a solvent, and may include a conductive agent as needed, and may further include a thickener.

[0116] The positive electrode active material may include a compound that can reversibly intercalate and deintercalate lithium ions (lithiated intercalation compound).

[0117] According to an exemplary embodiment, the positive active material may include lithium-nickel metal oxide. The lithium-nickel metal oxide may further include at least one of cobalt (Co), manganese (Mn), and aluminum (Al).

[0118] In some embodiments, the positive active material or the lithium-nickel metal oxide may include a layered structure or a crystal structure represented by the following Chemical Formula 1.

[0119] [Chemical formula 1]

[0120] Li x Ni a M b O 2+z

[0121] In Chemical Formula 1, 0.9≤x≤1.2, 0.6≤a≤0.99, 0.01≤b≤0.4, and -0.5≤z≤0.1 may be satisfied. As described above, M may include Co, Mn, and / or Al.

[0122] The chemical structure represented by Chemical Formula 1 represents the bonding relationship contained in the layered structure or crystal structure of the positive electrode active material, and does not exclude other additional elements. For example, M may include Co and / or Mn, and Co and / or Mn may be provided together with Ni as the main active element of the positive electrode active material. Chemical Formula 1 is provided to represent the bonding relationship of the main active elements, and it should be understood that Chemical Formula 1 is a formula including the introduction and substitution of additional elements.

[0123] In one embodiment, in addition to the main active element, an auxiliary element for enhancing the chemical stability of the positive electrode active material or the layered structure / crystal structure may be further included. The auxiliary element may be mixed together into the layered structure / crystal structure to form a bond, and it should be understood that this case is also included in the chemical structure represented by Chemical Formula 1.

[0124] The auxiliary element may include, for example, at least one of Na, Mg, Ca, Y, Ti, Hf, V, Nb, Ta, Cr, Mo, W, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Sr, Ba, Ra, P, or Zr. The auxiliary element may be an auxiliary active element that contributes to the capacity / power activity of the positive electrode active material together with Co or Mn, such as Al.

[0125] For example, the positive active material or the lithium-nickel metal oxide may include a layered structure or a crystal structure represented by the following Chemical Formula 1-1.

[0126] [Chemical formula 1-1]

[0127] Li x Ni a M1 b1 M2 b2 O 2+z

[0128] In Chemical Formula 1-1, M1 may include Co, Mn and / or Al. M2 may include the auxiliary elements described above. In Chemical Formula 1-1, 0.9≤x≤1.2, 0.6≤a≤0.99, 0.01≤b1+b2≤0.4, and -0.5≤z≤0.1 may be selected.

[0129] The positive electrode active material may further include a coating element or a doping element. For example, an element substantially the same as or similar to the auxiliary element may be used as the coating element or the doping element. For example, one of the above elements or a combination of two or more of the above elements may be used as the coating element or the doping element.

[0130] The coating element or the doping element may be present on the surface of the lithium-nickel metal oxide particle or permeate through the surface of the lithium-nickel metal oxide particle and be included in the bonding structure represented by the Chemical Formula 1 or Chemical Formula 1-1.

[0131] The positive active material may include a nickel-cobalt-manganese (NCM)-based lithium oxide. In this case, the NCM-based lithium oxide having an increased nickel content may be used.

[0132] Ni can be provided as a transition metal related to the power and capacity of a lithium secondary battery. Therefore, as described above, by using a high-content (high-nickel (High-Ni)) composition for the positive electrode active material, a high-capacity positive electrode and a high-capacity lithium secondary battery can be provided.

[0133] However, as the Ni content increases, the long-term storage stability and life stability of the positive electrode or secondary battery may decrease relatively, and side reactions with the electrolyte may also increase. However, according to exemplary embodiments, conductivity can be maintained by including Co, while life stability and capacity retention characteristics can be improved by Mn.

[0134] The content of Ni in the NCM-based lithium oxide (e.g., the mole fraction of Ni in the total moles of nickel, cobalt, and manganese) can be 0.6 or more, 0.7 or more, or 0.8 or more. In some embodiments, the content of Ni can be 0.8 to 0.95, 0.82 to 0.95, 0.83 to 0.95, 0.84 to 0.95, 0.85 to 0.95, or 0.88 to 0.95.

[0135] In some embodiments, the positive electrode active material may further include a lithium cobalt oxide-based active material, a lithium manganese oxide-based active material, a lithium nickel oxide-based active material, or a lithium iron phosphate (LFP)-based active material (e.g., LiFePO4).

[0136] In some embodiments, for example, the positive electrode active material may include a Mn-rich-based active material having a chemical structure or crystal structure represented by Chemical Formula 2, a Li rich layered oxide (LLO) / Over Lithiated Oxide (OLO)-based active material, or a Co-less-based active material.

[0137] [Chemical Formula 2]

[0138] p[Li2MnO3]·(1-p)[Li q JO2]

[0139] In Chemical Formula 2, 0 < p < 1, 0.9 ≤ q ≤ 1.2, and J may include at least one element among Mn, Ni, Co, Fe, Cr, V, Cu, Zn, Ti, Al, Mg, and B.

[0140] In the positive electrode, the content of the positive electrode active material can be 90-98% by weight based on the solid weight of the positive electrode mixture.

[0141] The binder serves to bond the positive electrode active material particles to each other and bond the positive electrode active material to the positive electrode current collector. The content of the binder can be 1.5-5% by weight based on the solid weight of the positive electrode mixture.

[0142] The binder may include, for example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-co-hexafluoropropylene), polyacrylonitrile, polymethylmethacrylate, nitrile rubber (NBR), polybutadiene rubber (BR), styrene-butadiene rubber (SBR), etc. In one embodiment, a PVDF-based binder may be used as a positive electrode binder.

[0143] In addition to the binder, a thickener may be further included to impart viscosity. As an embodiment, the thickener may include a thickener such as carboxymethyl cellulose (CMC). The content of the thickener may be 0.1-3 parts by weight relative to 100 parts by weight of the positive electrode active material.

[0144] The conductive agent may be added to enhance the conductivity of the positive electrode mixture layer and / or the mobility of lithium ions or electrons. The conductive agent may be appropriately used as long as it is a conductive material commonly used in the positive electrode of a secondary battery. For example, the conductive agent may include carbon-based conductive agents such as graphite, carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, vapor-grown carbon fiber (VGCF), carbon fiber, and / or metal-based conductive agents such as perovskite minerals such as tin, tin oxide, titanium oxide, LaSrCoO3, LaSrMnO3, but is not limited thereto. Based on the solid weight of the positive electrode mixture, the content of the conductive agent may be 0.1-5% by weight.

[0145] The positive electrode mixture may further include carbon fibers as distinguished from the conductive agent included in the negative electrode. When the carbon fibers are included in the positive electrode mixture, a linear lithium ion migration path can be provided around the carbon fibers, similar to the negative electrode, thereby shortening the migration path of the lithium ions.

[0146] The carbon fibers may be the same as those used in the negative electrode, and thus a detailed description thereof will be omitted.

[0147] The solvent may be an aqueous solvent such as water, or a non-aqueous solvent. The non-aqueous solvent may be used in the present invention as long as it is a solvent commonly used to prepare a positive electrode mixture of a secondary battery, for example, N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, but is not limited thereto.

[0148] Although not limited thereto, the solvent may be included so that the solid content of the positive electrode mixture slurry is 30-65 wt %.

[0149] The present invention includes the step of coating the positive electrode mixture slurry on the surface of the positive electrode current collector. The positive electrode current collector can be any metal commonly used in the manufacture of the positive electrode of the secondary battery and having good conductivity, for example, it can contain aluminum, nickel, titanium, stainless steel or their alloys, and can use aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and can be in various shapes such as sheet, foil, mesh, etc.

[0150] The thickness of the positive electrode current collector is not particularly limited, and may be, for example, 10-50 μm.

[0151] As described in the manufacturing process of the negative electrode, the positive electrode having the positive electrode mixture layer formed on the positive electrode collector may be manufactured by coating the positive electrode mixture slurry on one side or both sides of the positive electrode collector, performing a drying process, and then rolling.

[0152] The coating process can be carried out by gravure coating, slot extrusion coating, multi-layer simultaneous die coating, imprinting, blade coating, dip coating, rod coating, casting and the like, and is not limited thereto. The drying and calendering process can be carried out by the same method as the manufacturing method of the negative electrode, so the specific description is omitted.

[0153] A separator may be inserted between the positive electrode and the negative electrode. The separator may be configured to prevent a short circuit between the positive electrode and the negative electrode and generate a flow of ions. The separator may include a porous polymer film and a porous nonwoven fabric. The porous polymer film may include polyolefin-based polymers such as ethylene (Ethylene) polymers, propylene (Propylene) polymers, ethylene / butene (Ethylene / Butene) copolymers, ethylene / hexene (Ethylene / Hexene) copolymers, and ethylene / methacrylate (Ethylene / Methacrylate) copolymers.

[0154] The porous nonwoven fabric may include high melting point glass fiber, polyethylene terephthalate fiber, etc. The separator may also include a ceramic-based material. For example, inorganic particles may be coated on or dispersed in the polymer film, thereby improving heat resistance.

[0155] The separator may have a single-layer or multi-layer structure including the above-mentioned polymer film and / or nonwoven fabric.

[0156] The separator is not particularly limited, but for example, a separator having a thickness of about 10 to 40 μm may be used, for example, a separator having a thickness of 10 to 20 μm may be used.

[0157] According to a specific embodiment, in the case of the lithium secondary battery of the present invention, the electrode assembly can be housed in the battery housing and an electrolyte can be injected. The electrolyte comprises a non-aqueous organic solvent and a lithium salt. The non-aqueous organic solvent can provide a medium that can move ions involved in the electrochemical reaction of the battery.

[0158] According to an exemplary embodiment, as the electrolyte, a non-aqueous electrolyte may be used. The non-aqueous electrolyte may include a lithium salt as an electrolyte and an organic solvent.

[0159] The non-aqueous organic solvent acts as a medium that allows ions involved in the electrochemical reaction of the battery to move, and may include an organic compound that has sufficient solubility for the lithium salt and additives and is not reactive in the battery. For example, the organic solvent may include at least one of a carbonate-based solvent, an ester-based solvent, an ether-based solvent, a ketone-based solvent, an alcohol-based solvent, and an aprotic solvent.

[0160] The organic solvent may be propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate, diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, vinylene carbonate, methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (n-PA), 1,1-dimethylethyl acetate (DMEA), methyl propionate (MP), ethyl propionate (EP), fluoroethyl acetate (FEA), difluoroethyl acetate (DFEA), trifluoroethyl acetate (TFEA), dibutyl ether, tetraethylene glycol dimethyl ether (TEGDME), diethylene glycol dimethyl ether (DME), ether, DEGDME), dimethoxyethane, tetrahydrofuran (THF), 2-methyltetrahydrofuran, ethyl alcohol, isopropyl alcohol, dimethyl sulfoxide, acetonitrile, diethoxyethane, cyclopentane, γ-butyrolactone and propylene sulfite, etc. These can be used alone or in combination of two or more.

[0161] The lithium salt is dissolved in the organic solvent and functions as a supply source of lithium ions in the battery so that the lithium secondary battery can basically operate, and can provide a function of promoting movement of lithium ions between the positive electrode and the negative electrode.

[0162] The lithium salt may be, for example, Li + X - Indicates that, as the anion of the lithium salt (X - ), we can exemplify F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 -PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - etc., one kind of them may be used, or two or more kinds of them may be mixed and used.

[0163] The concentration of the lithium salt is not particularly limited, but may be used in the range of 0.1M to 2.0M.

[0164] The non-aqueous electrolyte may further include an additive. The additive may include, for example, a cyclic carbonate-based compound, a fluorine-substituted carbonate-based compound, a sultone-based compound, a cyclic sulfate-based compound, a cyclic sulfite-based compound, a phosphate-based compound, and a borate-based compound.

[0165] The cyclic carbonate-based compound may include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and the like.

[0166] The fluorine-substituted carbonate-based compound may include fluoroethylene carbonate (FEC) and the like.

[0167] The sultone-based compound may include 1,3-propane sultone, 1,3-propene sultone, 1,4-butane sultone, and the like.

[0168] The cyclic sulfate compound may include 1,2-ethylene sulfate, 1,2-propylene sulfate, etc.

[0169] The cyclic sulfite compound may include ethylene sulfite, butylene sulfite, etc.

[0170] The phosphate compound may include lithium difluoro bis-oxalato phosphate, lithium difluoro phosphate, etc.

[0171] The borate compound may include lithium bis(oxalate)borate, etc.

[0172] As described above, according to the present invention, by providing a linear lithium ion movement path in the negative electrode, the movement path of lithium ions can be shortened, and the fast charging characteristics can be improved.

[0173] Examples

[0174] Hereinafter, the present invention will be described in more detail by listing examples. The following examples are specific embodiments according to the present invention and do not limit the present invention.

[0175] Example 1

[0176] Based on the solid weight of the negative electrode mixture, 88.93% by weight of graphite, 8.10% by weight of SiO x (0 < x < 2), 1.3% by weight of styrene-butadiene rubber (SBR), 1.2% by weight of carboxymethyl cellulose (CMC), and 0.47% by weight of carbon fiber (average thickness of 7 μm and average length of 60 μm) were added to water to prepare a negative electrode mixture slurry. The solid content of the negative electrode mixture slurry was 46.3% by weight. SEM images of the carbon fiber were taken and the photos are shown in Figure 5 in.

[0177] The viscosity of the negative electrode mixture slurry was measured, and the results are shown in Table 1.

[0178] The negative electrode mixture slurry was coated on both sides of a copper foil, passed through a device applying a magnetic field on both the upper and lower sides of the electrode at a condition of 4000 Gauss, 4 seconds, and a moving speed of 2.1 m / s, and then dried at 200 °C for 1 minute and rolled to obtain a density of 1.60 g / cm3 of the negative electrode.

[0179] The cross-sectional structure of the obtained negative electrode was analyzed by XRM, and the image is shown in FIG. Figure 6 in (a).

[0180] Furthermore, the electrode resistance, interface resistance, black and white degree, P / O and average tortuosity factor of the obtained negative electrode were measured by the following method, and the result values ​​are shown in Table 1.

[0181] Electrode resistance and interface resistance: The resistance is measured using a four-terminal resistance tester.

[0182] P / O: This is a numerical value of the peak intensity of the (002) plane of graphite, which indicates the degree of in-plane orientation in the direction horizontal to the negative electrode current collector. It is an index indicating the orientation degree of the negative electrode active material. The smaller the value, the better the orientation degree.

[0183] Black and white degree and P / O: For the negative electrode, a black and white degree measuring instrument is used to measure the black and white degree of the coated negative electrode at 10 points at intervals of 10 mm in the width direction (minor axis direction) of the negative electrode, and the average is used as the black and white degree. In addition, the preferred orientation (P / O) of the orientation degree of the negative electrode active material is measured using XRD. The larger the black and white value, the better the vertical orientation degree of the negative electrode active material, and the smaller the P / O value, the better the vertical orientation degree of the negative electrode active material.

[0184] In order to evaluate the difference in black and white, a reference negative electrode (not passed through a device applying a magnetic field and dried and rolled under the same conditions) was manufactured, and the black and white of the reference negative electrode and the negative electrode of Example 1 were measured respectively, and the difference was calculated and shown in Table 1.

[0185] Average tortuosity factor: The tortuosity factor is calculated as Ls / Le, where Ls represents the thickness of the negative electrode mixture layer and Le represents the average distance that lithium ions travel through the negative electrode mixture layer and reach the negative electrode current collector.

[0186] The Le and Ls are measured by X-ray microscopy (XRM) (model: Xradia 620Versa, manufactured by ZEISS) for non-destructive high-resolution 3D imaging.

[0187] Comparative Example 1

[0188] Based on the solid weight of the negative electrode mixture, 88.93 wt% of graphite, 8.10 wt% of SiO x(0 < x < 2), 1.3 wt% styrene-butadiene rubber (SBR), 1.2 wt% carboxymethyl cellulose (CMC), and 0.47 wt% carbon nanotubes (CNT) (average thickness of 3.5 nm and average length of 25 μm) were added to water to prepare a negative electrode mixture slurry. The solid content of the negative electrode mixture slurry was 36.24 wt%.

[0189] The viscosity of the negative electrode mixture slurry was measured, and the results are shown in Table 1.

[0190] The negative electrode mixture slurry was coated on both sides of a copper foil in the same manner as in Example 1, and after drying while applying a magnetic field to the upper and lower surfaces of the electrode in the same manner as in Example 1, it was calendered to obtain a negative electrode with a density of 1.60 g / cm 3 of the negative electrode.

[0191] For the obtained negative electrode, the cross-sectional structure was analyzed by XRM, and the image is shown in Figure 6 (b).

[0192] For the obtained negative electrode, the electrode resistance, interface resistance, black and white difference value, P / O, and average tortuosity factor value were measured, and the results are shown in Table 1.

[0193] To evaluate the black and white difference value, a reference negative electrode (not dried and calendered under the same conditions by applying a magnetic field device) was manufactured, and the black and white degrees of the reference negative electrode and the negative electrode of Comparative Example 1 were measured respectively, and the difference was calculated and shown in Table 1.

[0194] [Table 1]

[0195]

[0196] From the viscosity values shown in Table 1, it can be seen that although the solid content of Example 1 is higher than that of Comparative Example 1, it also shows a lower viscosity value. From this result, it can be seen that Example 1 has a viscosity that can manufacture a negative electrode even when the solvent content is reduced, so it can contribute to improving the productivity of the negative electrode. It can be considered that the carbon fibers used in Example 1 and the CNTs of Comparative Example 1 have different density values of 1.75 - 1.93 g / cm 3 and 1.3 g / cm 3 respectively, thus providing a difference in volume fraction in the negative electrode mixture slurry, and therefore contributing to reducing the solvent content.

[0197] In addition, from Table 1, it can be seen that compared with Comparative Example 1, the electrode resistance value of the negative electrode of Example 1 has an equivalent level value. Therefore, it can be known that when using carbon fibers as shown in Example 1, equivalent conductivity can also be ensured.

[0198] Furthermore, it can be seen from the interface resistance value between the electrode and the current collector that, compared with the case of Comparative Example 1 containing CNTs, the electronic conductivity at the interface does not decrease in Example 1 even though carbon fibers are used.

[0199] Further, for the negative electrodes of Example 1 and Comparative Example 1, after coating the negative electrode mixture, the process of orientation by applying a magnetic field was performed, but the negative electrode of Example 1 showed a result of a decrease in the P / O value measured by XRD analysis compared with Comparative Example 1. From this result, it can be seen that this is because while orienting the negative electrode active material, the carbon fibers introduced into the negative electrode mixture layer support the oriented negative electrode active material, and provide a movement path for lithium ions through the pores around the carbon fibers.

[0200] Further, according to Example 1, when carbon fiber is included, the black and white difference between the obtained negative electrodes is larger, at 2.06, depending on whether a magnetic field is applied. On the other hand, in Comparative Example 1, the black and white difference between the obtained negative electrodes is smaller, at 1.14, depending on whether a magnetic field is applied.

[0201] In the case of Example 1, the carbon fibers contained in the negative electrode mixture layer support the magnetically oriented negative electrode active material, thereby maintaining the orientation. However, in the case of Comparative Example 1, since there is no support body that can support the oriented negative electrode active material after the magnetic orientation, the orientation of a part of the negative electrode active material cannot be maintained. Therefore, it is evaluated to show a small difference in black and white depending on whether a magnetic field is applied.

[0202] Furthermore, the average tortuosity factor of the negative electrode obtained in Example 1 is smaller than that in Comparative Example 1, and thus it is known that a more linear lithium ion migration path can be provided. From this result, it can be seen that the negative electrode of Example 1 has more excellent ion conductivity.

[0203] Further, from Figure 6 As can be seen in the figures (a) and (b), the negative electrode obtained in Example 1 has more developed pores than the negative electrode obtained in Comparative Example 1, and therefore has excellent porous characteristics. This can be evaluated as showing a tendency consistent with the average tortuosity factor value.

Claims

1. A negative electrode, comprising: Anode current collector; and a negative electrode mixture layer formed on at least one side of the negative electrode current collector, The negative electrode mixture layer comprises a negative electrode active material and carbon fibers. The average diameter of the cross section of the carbon fiber is 5-20 μm.

2. The negative electrode according to claim 1, wherein The negative electrode mixture layer includes: a first layer including a first surface in contact with the negative electrode current collector; and a second layer including a second surface located outside the negative electrode mixture layer opposite to the first surface. Wherein, the first layer contains the carbon fiber.

3. The negative electrode according to claim 2, wherein One or more negative electrode mixture layers are further included between the first layer and the second layer, and in the two adjacent layers, the negative electrode mixture layer close to the first surface has a higher content of carbon fibers than the negative electrode mixture layer close to the second surface.

4. The negative electrode according to claim 3, wherein The second layer may or may not contain carbon fibers.

5. The negative electrode according to claim 1, wherein The average length of the carbon fibers is 30-150 μm.

6. The negative electrode according to claim 1, wherein The carbon fiber has a g / cm 3 density.

7. The negative electrode according to claim 1, wherein The carbon fiber may be contained in an amount of 0.5 to 10% by weight relative to the total weight of the negative electrode mixture layer.

8. The negative electrode according to claim 1, wherein The negative electrode active material includes graphite.

9. The negative electrode according to claim 1, wherein The preferred orientation (P / O) value of the negative electrode according to XRD analysis is 0.45 or less.

10. The negative electrode according to claim 1, wherein The negative electrode active material has an orientation perpendicular to the negative electrode current collector.

11. The negative electrode according to claim 1, wherein The negative electrode has an average tortuosity factor value of 1.24 or less.

12. The negative electrode according to claim 1, wherein The negative electrode further includes a conductive agent, and the conductive agent further includes at least one selected from a particulate conductive agent having an average particle diameter of 10 to 500 nm and a fibrous conductive agent having an average fiber diameter of 10 to 500 nm. 13 . A secondary battery comprising a positive electrode and the negative electrode according to claim 1 .